Applications of Biopolymeric Gels in Medical Biotechnology - Yalinca, Zulal; Tuzmen, Sukru (John Wiley & Sons Ltd, 2019)
[Abstract Not Available]
Keywords: Drug-Delivery; Injectable Hydrogels; Biocompatibility; Polymers; Release; Biodegradation; Nanoparticles; Biomaterials; Copolymers; Strategies